Sentinel community Clostridium difficile infection (CDI) surveillance in Scotland, April 2013 to March 2014. (February 2016) - Banks, A.; Brown, Derek J.; Mather, Henry; Coia, John E.; Wiuff, Camilla
Abstract: Surveillance of Clostridium difficile infection (CDI) in Scotland does not currently distinguish between CDI cases from hospitals and the community. Therefore, the incidence of CDI in the community is unknown, and the burden of disease and the relationship with the hospital/healthcare setting is not well understood. A one-year sentinel community surveillance programme was initiated in collaboration with five Scottish health boards in 2013 (representing 36% of all CDI cases reported in Scotland). Inclusion criteria were all cases aged ≥15 years with a CDI diagnosis in the community or within 48 h following admission to hospital. CDI cases were categorised according to definitions used by the European Centre for Disease Prevention and Control. 256 CDI cases met the inclusion criteria, of which 158 (62%) were community-associated cases (CA-CDI). This represented 26% of all cases reported during the surveillance period by the participating health boards (n = 614). The overall CA-CDI incidence rate was 9.9 per 100 000 population per year. CA-CDI cases were more likely to be female and younger, compared to hospital acquired cases (HA-CDI). The total proportion of cases that had onset in the community was 27%. Ribotypes 015, 002, 078 and 005 were the most common types isolated from both CA-CDI and HA-CDI cases. There were no statistically significant differences between the proportion of types that were either CA-CDI or HA-CDI. Of the CA-CDI cases, 37% had not received antibiotics in the 12 weeks preceding CDI diagnosis, 4% were resident in care homes, and the case-fatality rate for CA-CDI cases was 5.6% (with a 30-day mortality rate for CA-CDI of 0.44 per 100 000 population per year). This study has shown that a substantial proportion of CDI cases reported in Scotland are community associated and that there are close links between the community and healthcare settings. It is therefore essential to monitor the trends in CDI in the community at a national level. The study also provides evidence for the need to examine the feasibility for development of interventions to reduce the burden in the community in addition to hospitals. Highlights: An estimated 26% of CDI cases reported in Scotland are community associated. Ribotypes 015, 002, 078 and 005 were the most commonly isolated types suggesting similar environmental exposures. Reinforcing interventions already in place in the healthcare setting should help to reduce the burden in the community. Further investigation of community sources and potential links with hospital cases will be required. Raising the awareness of CDI in the community setting among general practitioners and the public will be helpful.